Organisational determinants of employees’ affective commitment in pharmaceutical multinationals: mediation by perceived corporate social responsibility - Ng, Angeline; Raghavan, Santhi; Ho, Jo Ann (Emerald Publishing, 2024)
Purpose: This quantitative study aims to examine the mediating role of perceived corporate social responsibility (CSR) between organisational practices and affective commitment. Code of ethics, ethics training, transformational leadership and ethical climate were investigated as factors of perceived CSR. Design/methodology/approach: This research model was evaluated using structural equation modelling and survey data from 184 employees of Malaysian pharmaceutical multinationals. Findings: Perceived CSR mediated the relationship between code of ethics, transformational leadership, ethical climate and affective commitment. Practical implications: The CSR investments aimed at developing an effective ethics programme, transformational leadership practices and ethical climate could improve organisational competitiveness by strengthening employees’ perceived CSR and affective commitment. Originality/value: The systematic investigation of various organisational controls that establish a corporate environment of ethics and social responsibility sets a precedent for past piecemeal approaches. The existing body of knowledge is based on Western countries, which revealed insights unique to pharmaceutical multinationals in a transitional Asian economy.